Active synovitis in the presence of osteitis predicts residual synovitis in patients with rheumatoid arthritis with a clinical response to treatment. (3rd February 2017) - Fukae, Jun; Tanimura, Kazuhide; Isobe, Masato; Kitano, Akemi; Henmi, Mihoko; Nakai, Maria; Aoki, Yuko; Sakamoto, Fumihiko; Narita, Akihiro; Ito, Takeya; Mitsuzaki, Akio; Matsuhashi, Megumi; et al.
Abstract: Aim: To clarify the relationship between active synovitis/osteitis and subsequent residual synovitis (R‐synovitis) in patients with rheumatoid arthritis (RA). Methods: Three hundred and twenty finger joints of 16 patients with active RA at baseline (Disease Activity Score with 28 joints – erythrocyte sedimentation rate > 3.2) who subsequently achieved clinical low disease activity or remission afterwards were analyzed. Synovial vascularity (SV) was assessed according to a semi‐quantitative ultrasound score (grades 0–3). Active synovitis was defined by SV positivity at baseline. R‐synovitis was defined by the presence of grade > 2 SV at the 24th week. Osteitis was detected by magnetic resonance imaging (MRI) at baseline as trabecular bone lesions with water content and indistinct margins. Results: Ultrasonography detected active synovitis in 116 joints at baseline. Forty‐seven joints had R‐synovitis at the 24th week. MRI detected osteitis in 12 joints at baseline. The presence of active synovitis with osteitis at baseline was significantly correlated with R‐synovitis at the 24th week. Conclusions: Active synovitis in the presence of osteitis predicted R‐synovitis regardless of whether there was a clinical improvement in RA.